2019
DOI: 10.1002/ptr.6379
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins ameliorate palmitate‐induced inflammation and insulin resistance in 3T3‐L1 adipocytes

Abstract: Increased adiposity has been associated with adipose tissue low‐grade inflammation leading to insulin resistance. Adipocyte differentiation inhibitors are expected to be effective in preventing obesity and related diseases. Anthocyanins (ACNs) are associated to enhanced adipocyte function and protection from metabolic stress. Herein, we evaluated the in vitro protective effects of an ACN rich extract against palmitic acid (PA)‐induced hypertrophy, inflammation, and insulin resistance in 3T3‐L1 adipocytes. ACN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…In fact, in murine 3T3-L1 exposed to PA we have shown the ability of C3G, as well as of an anthocyanin-rich extract, to counteract the activation of NF-кB pathway, the master regulator of inflammatory machinery, induced by an excess of this FFA. [18,19] Moreover, the anti-inflammatory activity of anthocyanins has been also demonstrated in 3T3-L1 adipocytes exposed to TNF-α through the inhibition of NF-кB pathway as well as through the increase of adiponectin and the reduction of leptin, two markers considered as inflammatory modulators known to play a crucial role in insulin sensitivity and body energy balance. [38,40] However, articles reporting the effects of C3G on murine adipocytes demonstrated that the minimum effective C3G concentration was > 5 μM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, in murine 3T3-L1 exposed to PA we have shown the ability of C3G, as well as of an anthocyanin-rich extract, to counteract the activation of NF-кB pathway, the master regulator of inflammatory machinery, induced by an excess of this FFA. [18,19] Moreover, the anti-inflammatory activity of anthocyanins has been also demonstrated in 3T3-L1 adipocytes exposed to TNF-α through the inhibition of NF-кB pathway as well as through the increase of adiponectin and the reduction of leptin, two markers considered as inflammatory modulators known to play a crucial role in insulin sensitivity and body energy balance. [38,40] However, articles reporting the effects of C3G on murine adipocytes demonstrated that the minimum effective C3G concentration was > 5 μM.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of biological activities of anthocyanins has been reported in animal models, including antioxidant, anti‐inflammatory, anti‐atherosclerosis, and anti‐hyperglycemic activities [17] . In two recent studies we demonstrated that both cyanidin‐3‐ O ‐glucoside (C3G) and an anthocyanin rich extract showed not only a high antioxidant and anti‐inflammatory activity, but also a marked anti‐obesity and insulin sensitizing effect, markedly reducing hypertrophy, inflammation, and insulin resistance induced by high concentration of FFAs in murine 3T3‐L1 adipocytes [18,19] …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…When HAEC were exposed to the series of anthocyanins and respective metabolites, they found a reduction of ICAM-1 and VCAM-1 mRNA by the anthocyanins, with a reduction in IL-6 mRNA by the metabolites [ 66 ]. Palmitate-induced inflammation was also studied by Muscara et al (2019) in murine adipocytes [ 67 ]. They found that anthocyanins specifically from bilberry ( Vaccinium myrtillus ) and blackcurrant ( Ribes nigrum ) had a dose-dependent attenuating effect on NF-kB and IL-6 mRNA level.…”
Section: Inflammationmentioning
confidence: 99%
“…Anthocyanins treatment suppressed lipid accumulation, PPAR-γ level, and NF-κB activation in palmitic acid-induced 3T3-L1 adipocytes in a dose-dependent manner. Moreover, anthocyanins treatment improved insulin sensitivity and suppressed the comorbidities of obesity in vitro [ 83 ]. Cyanidin and C3G-rich ethanolic extract of Vigna unguiculata showed significant pancreatic lipase inhibition in vitro, which indicated that V. unguiculata anthocyanins have anti-obesity potential [ 84 ] ( Table 3 ).…”
Section: Anthocyanins and Obesitymentioning
confidence: 99%